Systolic blood pressure time in range and long-term clinical outcomes in patients with ischaemic cardiomyopathy. (3rd October 2022) - Zhou, Z; Fu, G; Jian, B; Liang, M; Chen, G; Wu, Z
Abstract: Background: The relationship between systolic blood pressure (SBP) control and long-term clinical outcomes in patients with ischaemic cardiomyopathy remains unclear. It has been previously reported that either too high or too low SBP may lead to a poorer prognosis. But current SBP control metrics may not take into account the possible effects of fluctuating SBP overtime on patients. Purpose: This study aimed to estimate the association between time in range (TIR) of SBP and long-term clinical outcomes in patients with ischaemic cardiomyopathy. Methods: This study was a post-hoc analysis of The Surgical Treatment of Ischaemic Heart Failure (STICH) trial, a randomized controlled trial with two hypotheses that enrolled participants with coronary artery disease and left ventricular ejection fraction ≤35%. The SBP target range of the TIR was defined as 110 to 130 mmHg and the SBP TIR was calculated by linear interpolation method. Patients were equally divided into four groups by quartiles of TIR. Multivariable-adjusted Cox proportional hazards regression models were constructed to compare the effects of different levels of TIR on a 10-year prognosis. The primary outcome was all-cause mortality. Subgroup analyses were performed according to whether patients were assigned to coronary artery bypass grafting (CABG) or medical therapy (MED), and in populations with different baseline SBP. Results: A total of 1194 eligible patients were included according to the purpose of our study. Compared with patients in the quartile 4 group (TIR 77.87–100%), the fully adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) of all-cause mortality were 1.32 (0.98–1.78) for quartile 3 group (TIR 54.81–77.63%), 1.40 (1.03–1.90) for quartile 2 group (TIR 32.59–54.67%), and 1.53 (1.14–2.04) for quartile 1 group (TIR 0–32.56%) (P for trend = 0.005). When evaluated TIR as a continuous variable, per 1-SD decrement (29.28%) in TIR significantly increased the incidence of all-cause mortality [1.15 (1.04–1.26)]. Similarly, the decrement in TIR significantly elevated the risk of cardiovascular (CV) mortality and the risk of all-cause mortality plus CV rehospitalization. Consistent results were also observed in subgroup analyses of either CABG or MED, or different baseline SBP, indicating the robustness of our findings. Conclusions: This study suggested that in patients with ischaemic cardiomyopathy, a higher SBP TIR was significantly associated with a decreased risk of all-cause mortality, CV mortality and the composite of all-cause mortality plus CV rehospitalization, regardless of whether the patient received CABG or MED, and the level of baseline SBP. Our findings support that TIR might be a substitutable metric of SBP control for long-term clinical outcomes in patients with ischaemic cardiomyopathy. Funding Acknowledgement: Type of funding sources: None.